Method for manufacturing solid electrolyte sheet and solid electrolyte sheet

By stacking and filling three-dimensional structures on the solid electrolyte layer, the problem of lithium ion insertion and disengagement is solved, the battery output performance is improved, and interface peeling and short circuit are suppressed, thereby achieving higher energy density and stability.

CN115133127BActive Publication Date: 2024-12-20HONDA MOTOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210183967.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2022-02-28
Publication Date
2024-12-20
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

In the manufacturing of existing solid electrolyte layers, the support on the side of the substrate causes the lithium ion insertion and disengagement, increase internal resistance, reduce battery output performance, and there is a risk of interface peeling and short circuit.

Method used

The solid electrolyte slurry is applied to the substrate to form a solid electrolyte layer, and a thin sheet-like three-dimensional structure is laminated on it. The slurry is applied inside and above to dry it to form a thin sheet filled with solid electrolyte. The three-dimensional structure The body is arranged in the center of the thickness direction to avoid interface peeling and short circuit.

Benefits of technology

By allowing lithium ions to be inserted and disengaged smoothly, the battery output performance is improved, the adhesion between the solid electrolyte layer and the electrode layer is enhanced, interface peeling and short circuit are suppressed, and the energy density and stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115133127B_ABST
    Figure CN115133127B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a solid electrolyte sheet and a solid electrolyte sheet, wherein the method for manufacturing a solid electrolyte sheet can improve battery output performance by allowing lithium ions to smoothly insert and detach from a solid electrolyte layer to an electrode, and can inhibit interface peeling or short circuiting between the solid electrolyte layer and the electrode layer by improving the adhesion between the solid electrolyte layer and the electrode layer. The method for manufacturing a solid electrolyte sheet of the present invention includes: a first step of applying a slurry containing a solid electrolyte to a substrate; a second step of forming a solid electrolyte layer by drying the slurry on the substrate; a third step of stacking a sheet-like three-dimensional structure on the upper surface of the solid electrolyte layer; a fourth step of applying a slurry containing a solid electrolyte to the interior and upper portion of the three-dimensional structure; and a fifth step of drying the slurry inside and on the upper portion of the three-dimensional structure to obtain a solid electrolyte sheet filled with a solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a solid electrolyte sheet and the solid electrolyte sheet. Background Art

[0002] In recent years, with the popularity of various electrical / electronic devices such as automobiles, personal computers, and mobile phones, the demand for high-capacity, high-output batteries has rapidly expanded. For example, solid batteries with solid electrolyte materials are superior to existing batteries with organic electrolytes as electrolytes because the electrolyte is non-flammable, so they are excellent in terms of improved stability and higher energy density, and are currently attracting much attention (for example, see Patent Document 1).

[0003] Solid-state batteries are composed of a laminated body composed of a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. The solid electrolyte layer has the function of conducting ions and the function of a separator to prevent short circuits between the negative electrode active material layer and the positive electrode active material layer.

[0004] Here, for the purpose of improving volume energy density and reducing resistance, the following method is disclosed: in order to reduce the thickness of the solid electrolyte layer and suppress pinhole formation and the short circuit caused by it, a two-layer solid electrolyte layer is manufactured using the same solid electrolyte (for example, refer to Patent Document 2).

[0005] In addition, as an example of a general method for manufacturing a solid electrolyte layer using a three-dimensional structural material such as a non-woven fabric as a support, there is the following method: a porous support is placed on a peelable substrate, a slurry containing a solid electrolyte is applied from the support, and then the peelable substrate is peeled off to thereby manufacture a solid electrolyte layer.

[0006] [Prior art literature]

[0007] [Patent Document]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 2014-026747

[0009] [Patent Document 2] Japanese Patent No. 5930035 Summary of the invention

[0010] [Problems to be solved by the invention]

[0011] However, in the conventional production of solid electrolyte layers, there are a number of problems to be solved as described below.

[0012] First, in the solid electrolyte sheet manufactured using a three-dimensional structure as a support on a strippable substrate, there is a support near the surface of the face on the substrate side. Therefore, when the face of the substrate side after the substrate is stripped and the electrode layer are bonded, it is easy to produce an interface peeling on the bonding surface of the face and the electrode layer. In addition, because there is a support near the bonding surface, the insertion and separation of lithium ions are hindered, so the internal resistance increases and the battery output performance decreases. And then, because there is a support near the bonding surface, there is also a concern about short circuit.

[0013] The present invention is completed in view of the above-mentioned problems to be solved, and its purpose is to provide a method for manufacturing a solid electrolyte sheet and a solid electrolyte sheet. The method for manufacturing a solid electrolyte sheet can improve the battery output performance by allowing lithium ions to smoothly insert and detach from the solid electrolyte layer to the electrode, and can inhibit interface peeling or short circuit between the solid electrolyte layer and the electrode layer by improving the adhesion between the solid electrolyte layer and the electrode layer.

[0014] [Technical means to solve the problem]

[0015] (1) The present invention provides a method for manufacturing a solid electrolyte sheet, wherein the solid electrolyte sheet is filled with a solid electrolyte, and the manufacturing method comprises: a first step of applying a slurry containing a solid electrolyte on a substrate; a second step of forming a solid electrolyte layer by drying the slurry on the substrate; a third step of stacking a thin sheet-like three-dimensional structure on the upper surface of the solid electrolyte layer; a fourth step of applying a slurry containing a solid electrolyte on the inside and upper part of the three-dimensional structure; and a fifth step of obtaining a solid electrolyte sheet filled with a solid electrolyte by drying the slurry on the inside and upper part of the three-dimensional structure.

[0016] (2) The method for producing a solid electrolyte sheet according to (1), wherein the three-dimensional structure may be a nonwoven fabric.

[0017] (3) In addition, the present invention provides a solid electrolyte sheet filled with a solid electrolyte and comprising: a thin sheet-shaped three-dimensional structure, which is arranged in the center in the thickness direction and is filled with a solid electrolyte; and a solid electrolyte layer formed in a manner covering the front and back sides of the three-dimensional structure.

[0018] (4) The solid electrolyte sheet according to (3), wherein the three-dimensional structure may be a non-woven fabric.

[0019] [Effects of the Invention]

[0020] According to the present invention, a method for manufacturing a solid electrolyte sheet and a solid electrolyte sheet can be provided. The method for manufacturing a solid electrolyte sheet can improve the battery output performance by allowing lithium ions to smoothly insert and detach from the solid electrolyte layer into the electrode, and can inhibit interface peeling or short circuiting between the solid electrolyte layer and the electrode layer by improving the adhesion between the solid electrolyte layer and the electrode layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a diagram showing a method for producing a solid electrolyte sheet according to one embodiment of the present invention.

[0022] Figure 2 It is a diagram showing a conventional method for producing a solid electrolyte sheet.

[0023] Figure 3 This is a cross-sectional view showing a solid electrolyte sheet according to an embodiment of the present invention in comparison with a conventional solid electrolyte sheet.

[0024] Figure 4 This is a cross-sectional SEM (Scanning Electron Microscope) image of a solid electrolyte sheet of an example.

[0025] Figure 5 This is a cross-sectional SEM image of a solid electrolyte sheet of a comparative example.

[0026] Figure 6 This is a graph showing the relationship between the thickness of the solid electrolyte sheet and the DC resistance value in Examples and Comparative Examples.

[0027] Figure 7 This is a graph showing the relationship between the thickness of the solid electrolyte sheet and the battery capacity in Examples and Comparative Examples. DETAILED DESCRIPTION

[0028] Hereinafter, one embodiment of the present invention will be described in detail with reference to the drawings.

[0029] <Method for producing solid electrolyte sheet>

[0030] Figure 1 1 is a diagram showing a method for manufacturing a solid electrolyte sheet according to an embodiment of the present invention. Figure 1As shown, the method for manufacturing a solid electrolyte sheet of the present embodiment includes: a first step of applying a slurry containing a solid electrolyte on a substrate; a second step of forming a solid electrolyte layer by drying the slurry on the substrate; a third step of stacking a thin sheet-like three-dimensional structure on the upper surface of the solid electrolyte layer; a fourth step of applying a slurry containing a solid electrolyte inside and on the upper part of the three-dimensional structure; and a fifth step of obtaining a solid electrolyte sheet filled with a solid electrolyte by drying the slurry inside and on the upper part of the three-dimensional structure.

[0031] The method for producing a solid electrolyte sheet according to the present embodiment comprises the first step to the fifth step, thereby producing a solid electrolyte-filled sheet material in which a three-dimensional structure is impregnated with a solid electrolyte slurry.

[0032] [1st step]

[0033] The first step is to apply a slurry containing a solid electrolyte onto a substrate (see Figure 1 (a)). In the method for manufacturing a solid electrolyte sheet of the present embodiment, a slurry containing a solid electrolyte is applied to a peelable substrate. A known method can be used for applying the slurry containing a solid electrolyte. For example, a doctor blade coating method, a spraying method, a sputtering method, etc. can be mentioned.

[0034] The coating thickness of the slurry containing the solid electrolyte is preferably 2.0 to 4.5 times the thickness of the solid electrolyte sheet after pressurization.

[0035] The substrate used in the method for producing the solid electrolyte sheet of the present embodiment is preferably a substrate having good peeling performance for the solid electrolyte layer. In addition, the substrate having good peeling performance for the solid electrolyte layer is preferably a substrate having a heat resistance to the extent that it will not be deformed or damaged by heat during the drying process of the slurry containing the solid electrolyte in the second and fourth steps.

[0036] The slurry containing the solid electrolyte is not particularly limited, as long as it is a slurry containing at least a solid electrolyte capable of conducting lithium ions between the positive electrode and the negative electrode. For example, as such a solid electrolyte, an oxide-based electrolyte or a sulfide-based electrolyte can be cited. In addition, as required, other components such as an adhesive may also be added to the slurry containing the solid electrolyte. In addition, in the case of further adding an electrode active material to the slurry containing the solid electrolyte, it can be applied to the manufacturing method of the electrode layer.

[0037] The slurry containing the solid electrolyte preferably contains lithium element. When the solid electrolyte contains lithium element, the lithium ion conductivity can be improved.

[0038] Specifically, the solid electrolyte is preferably a substance containing at least lithium sulfide and containing one or more compounds selected from the following group as the second component, the group containing silicon sulfide, phosphorus sulfide and boron sulfide, and the solid electrolyte is particularly preferably Li 2 SP 2 S 5 It is known that the lithium ion conductivity of this sulfide-based solid electrolyte is higher than that of other inorganic compounds, except for Li 2 SP 2 S 5 In addition, it can also include SiS 2 ,GeS 2 , B 2 S 3 In addition, Li can be appropriately added to the solid electrolyte. 3 PO 4 Or halogen, halogen compound, etc.

[0039] As the solid electrolyte, a lithium ion conductor composed of an inorganic compound may be contained as an inorganic solid electrolyte. Examples of the lithium ion conductor include: Li 3 N、LISICON、LIPON(Li 3+y PO 4-x N x )、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S 4 )、Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 (LATP).

[0040] The solid electrolyte may be amorphous, glassy, ​​crystalline (crystallized glass), or any other structure. 2 SP 2 S 5 In the case of sulfide-based solid electrolytes, the lithium ion conductivity of the amorphous body is 10 -4 Scm -1 On the other hand, the lithium ion conductivity of the crystalline body is 10 -3 Scm -1 .

[0041] The solid electrolyte used in the method for producing a solid electrolyte sheet of the present embodiment preferably contains phosphorus and / or sulfur. When the solid electrolyte further contains phosphorus and / or sulfur, the ion conductivity of the obtained solid electrolyte sheet can be improved.

[0042] [Step 2]

[0043] The second step is a step of drying the slurry containing the solid electrolyte applied on the substrate using a drying device to form a solid electrolyte layer (see Figure 1 (b)).

[0044] As a method for forming a solid electrolyte layer by drying a slurry containing a solid electrolyte applied on a substrate, any known method may be used as long as the shape of the slurry containing a solid electrolyte applied in a thin film is not destroyed when heated. For example, a method of drying the slurry containing a solid electrolyte by heating a substrate and the slurry containing a solid electrolyte applied on the substrate on a heating plate; and a method of using other known drying devices such as an electric furnace instead of a heating plate.

[0045] [Step 3]

[0046] The third step is a step of laminating a three-dimensional structure on the upper surface of the solid electrolyte layer formed in the second step (see Figure 1 (c)). As a method for stacking the three-dimensional structure on the upper surface of the solid electrolyte layer, a known method can be adopted. For example, a method of simply placing the three-dimensional structure on the upper surface of the solid electrolyte layer can be cited.

[0047] The three-dimensional structure used in the method for manufacturing the solid electrolyte sheet of the present embodiment can be exemplified by a screen, a woven fabric, a non-woven fabric, an embossed body, a perforated body, an extended body, a foamed body, etc., preferably a non-woven fabric. If the three-dimensional structure is a non-woven fabric, then in the method for manufacturing the solid electrolyte sheet of the present embodiment, the solid electrolyte slurry can be quickly impregnated into the three-dimensional structure, so it is easy to reduce the manufacturing cost consumed by the impregnation.

[0048] The material of the three-dimensional structure is not particularly limited, as long as it is a sheet material that can form a self-supporting solid electrolyte sheet. Examples include polyethylene terephthalate, nylon, aramid, Al 2 O 3 , glass, metal, etc. In this case, polyethylene terephthalate, nylon, aramid, Al 2 O 3 In the case of using a non-conductive material such as glass, the present invention can be applied to a method for manufacturing a solid electrolyte sheet. In addition, in the case of using a conductive material such as a metal material as the material of the three-dimensional structure, the present invention can be applied to a method for manufacturing an electrode layer.

[0049] The porosity of the three-dimensional structure is preferably in the range of 60% to 95%, more preferably 70% to 90%, and particularly preferably 80% to 90%.

[0050] The thickness of the three-dimensional structure is preferably in the range of 5 to 30 μm. The thickness of the three-dimensional structure is further preferably 5 to 20 μm, and particularly preferably 10 to 20 μm. When the thickness is less than 5 μm, there is a concern that a short circuit between electrodes may occur when a battery is formed. On the other hand, when the thickness exceeds 30 μm, it is difficult to apply the solid electrolyte slurry to the three-dimensional structure, and therefore it is difficult to achieve a solid electrolyte sheet with a high energy density.

[0051] [Step 4]

[0052] The fourth step is a step of applying a slurry containing a solid electrolyte to the interior and upper portion of the three-dimensional structure (see Figure 1 (d)). A slurry containing a solid electrolyte is applied from the upper surface of the three-dimensional structure. While applying the slurry to the entire interior of the three-dimensional structure, a slurry containing a solid electrolyte is also applied to the upper part of the three-dimensional structure. As a method for applying a slurry containing a solid electrolyte from the upper surface of the three-dimensional structure, the method used in the second step can be adopted.

[0053] In the fourth step, the slurry containing the solid electrolyte is preferably applied in a manner that the three-dimensional structure is arranged in the approximate center of the thickness direction of the solid electrolyte sheet. By applying the slurry containing the solid electrolyte in a manner that the three-dimensional structure is arranged in the approximate center of the thickness direction of the solid electrolyte sheet, the three-dimensional structure is not exposed to the surface of the solid electrolyte sheet material, so that the interface peeling between the solid electrolyte sheet and the electrode layer can be suppressed, which may occur when the solid electrolyte sheet formed by the fifth step is used to make a battery. In addition, the movement and insertion and separation of lithium ions caused by the three-dimensional structure generated when making a battery can be suppressed.

[0054] The coating thickness of the slurry containing a solid electrolyte is preferably such that the three-dimensional structure is provided at the approximately central portion of the thickness direction of the solid electrolyte sheet when drying is completed. More specifically, the coating thickness of the slurry containing a solid electrolyte when applied in the fourth step is preferably the thickness obtained by subtracting the thickness of the three-dimensional structure from the coating thickness of the slurry containing a solid electrolyte when applied in the second step.

[0055] [Step 5]

[0056] The fifth step is a step of drying the slurry containing the solid electrolyte inside and on the top of the three-dimensional structure to form a solid electrolyte sheet having the three-dimensional structure inside the solid electrolyte layer (see Figure 1 (e) and Figure 1 (f)). Regarding the drying method, the same method as the second step of this embodiment can be adopted.

[0057] The thickness of the solid electrolyte sheet obtained after the drying treatment is preferably 1.5 to 2.5 times the thickness of the solid electrolyte sheet after the pressurization.

[0058] In addition, regarding the solid electrolyte sheet obtained after drying in the fifth step, the peelable substrate may or may not be peeled before being used as a battery component to manufacture a solid battery. In addition, after the solid electrolyte sheet is pressurized, the positive electrode layer, the solid electrolyte sheet, and the negative electrode layer are stacked and pressurized in this order, thereby manufacturing a solid battery. A solid battery can also be manufactured by stacking and pressurizing the positive electrode layer, the solid electrolyte sheet, and the negative electrode layer in this order.

[0059] In addition, the method for manufacturing a solid electrolyte sheet of the present invention can be applied to the method for manufacturing the solid electrolyte sheet. Moreover, by making various additions, changes, or deletions without departing from the main purpose of the invention, it can also be applied to the method for manufacturing a sheet material containing a solid electrolyte such as an electrode layer.

[0060] <Solid electrolyte sheet>

[0061] A solid electrolyte sheet according to an embodiment of the present invention comprises: a sheet-like three-dimensional structure, which is arranged in the center in the thickness direction and filled with a solid electrolyte; and a solid electrolyte layer, which is formed in a manner of covering the front and back sides of the three-dimensional structure, respectively. More specifically, the solid electrolyte sheet according to the present embodiment is a solid electrolyte sheet manufactured by the method for manufacturing the solid electrolyte sheet according to the present embodiment. For the solid electrolyte layer and the three-dimensional structure, an electrode material that can be used in the method for manufacturing the solid electrolyte sheet can be preferably used.

[0062] Figure 3 It is a cross-sectional view showing the solid electrolyte sheet of the present embodiment in comparison with a conventional solid electrolyte sheet. Figure 3 (a) is a solid electrolyte sheet of this embodiment, Figure 3 (b) is an existing solid electrolyte sheet. Figure 3 As shown in (b), in the conventional solid electrolyte sheet 100, a three-dimensional structure 50 such as a nonwoven fabric exists near the negative electrode layer 120 side, so that the lithium ions moving from the positive electrode layer 110 to the negative electrode layer 120 are hindered by the three-dimensional structure near the negative electrode layer 120, and the movement speed of the lithium ions is slowed down. As a result, the insertion and extraction of lithium ions into and out of the electrode is hindered, the internal resistance increases, and the output performance of the battery is reduced.

[0063] In contrast, Figure 3As shown in (a), in the solid electrolyte sheet 10 of this embodiment, the three-dimensional structure 5 such as nonwoven fabric is arranged at the approximate center of the thickness direction of the solid electrolyte sheet 10. Therefore, the lithium ions moving from the positive electrode layer 11 to the negative electrode layer 12 can move along the three-dimensional structure 5 at the approximate center of the thickness direction, so the movement of the lithium ions will not be seriously hindered, and the movement speed will not be greatly reduced. As a result, compared with the prior art, the insertion and removal of lithium ions into the electrode can be smoothly carried out, and the output performance of the battery is improved.

[0064] Therefore, according to the manufacturing method of the solid electrolyte sheet and the solid electrolyte sheet of the present embodiment, the battery output performance can be improved by allowing lithium ions to be smoothly inserted and separated from the solid electrolyte layer to the electrode, and the interface peeling or short circuit between the solid electrolyte layer and the electrode layer can be suppressed by improving the adhesion between the solid electrolyte layer and the electrode layer.

[0065] The solid electrolyte sheet of the present embodiment can be applied as a solid electrolyte layer to a solid battery by applying pressure.

[0066] The present invention is not limited to the above-described embodiments, and modifications and improvements within the scope that can achieve the object of the present invention are included in the present invention.

[0067] [Example]

[0068] Next, examples of the present invention will be described, but the embodiments of the present invention are not limited to these examples.

[0069] <Example>

[0070] [Fabrication of solid electrolyte sheets]

[0071] A slurry of a solid electrolyte is prepared by mixing a solid electrolyte with a solvent. After applying the slurry of the solid electrolyte to a strippable substrate, it is dried on a hot plate, thereby forming a solid electrolyte layer on the substrate. Next, after a non-woven fabric as a three-dimensional structure is placed on the upper surface of the solid electrolyte layer, the slurry of the solid electrolyte is applied again from the upper part of the three-dimensional structure. Then, it is dried on a hot plate again, and after the substrate is peeled off, it is pressurized to obtain a solid electrolyte sheet of the embodiment. The solid electrolyte sheet of the embodiment is made in multiple pieces by changing the coating thickness of the solid electrolyte slurry, and is used for the following evaluation test.

[0072] [Production of solid state batteries]

[0073] A positive electrode layer containing NCM as a positive electrode active material, the solid electrolyte sheet, and a negative electrode layer containing graphite as a negative electrode active material were stacked in this order and then pressed to produce a solid battery for evaluation. The following evaluation test was performed using the solid battery for evaluation.

[0074] <Comparative Example>

[0075] The nonwoven fabric used as the three-dimensional structure in the example is placed on a removable substrate, and a slurry containing a solid electrolyte prepared in the same manner as in Example 1 is applied to the nonwoven fabric. Next, after drying using a hot plate, the removable substrate is peeled off and then pressed to obtain a solid electrolyte sheet of the comparative example. Using the obtained solid electrolyte sheet, a solid battery for evaluation is prepared in the same order as in the example. The solid electrolyte sheet of the comparative example is also prepared in multiple pieces by changing the coating thickness of the solid electrolyte slurry, and used in the following evaluation test.

[0076] [Cross-section SEM observation]

[0077] The obtained solid electrolyte sheets of Examples and Comparative Examples were subjected to cross-sectional SEM observation.

[0078] Figure 4 : is a cross-sectional SEM image of the solid electrolyte sheet of the embodiment. Figure 4 As shown, it was confirmed that in the solid electrolyte sheet of the example, the nonwoven fabric as a three-dimensional structure was arranged substantially in the center in the thickness direction of the solid electrolyte sheet. Figure 5 FIG. 4 is a cross-sectional SEM image of a solid electrolyte sheet of a comparative example. Figure 5 As shown, it was confirmed that in the solid electrolyte sheet of the comparative example, the nonwoven fabric as a three-dimensional structure was arranged near one surface.

[0079] [DC resistance measurement test]

[0080] The obtained evaluation battery was subjected to a DC resistance measurement test. The evaluation battery was set to a state of 50% charge rate (SOC (State of Charge)) and discharged at a constant current, and the DC resistance at 10 seconds was measured.

[0081] The results are shown in Figure 6 .

[0082] Figure 6 Graph showing the relationship between the thickness and DC resistance of the solid electrolyte (SE) sheet after pressurization in the examples and comparative examples. Figure 6 In the graph, the vertical axis represents the respective measured values ​​as relative values, with the maximum value among the values ​​of DC resistance obtained in the present test being set to 1.

[0083] like Figure 6As shown, it was confirmed that the solid battery using the solid electrolyte sheet of the embodiment had a lower DC resistance than the solid battery using the solid electrolyte sheet of the comparative example regardless of the thickness of the solid electrolyte sheet. Based on this result, it was confirmed that the output performance of the battery using the solid electrolyte sheet of the embodiment was improved compared with the solid electrolyte sheet of the comparative example.

[0084] [Short circuit suppression effect evaluation test]

[0085] The obtained evaluation battery was subjected to a short-circuit suppression effect evaluation test.

[0086] The evaluation battery was brought to a state of charge rate (SOC) of 20% and allowed to stand for 10 days without flowing a current through the evaluation battery, and then the open circuit voltage was measured.

[0087] When the voltage between the positive and negative terminals of the solid battery is 0.000 V, a short circuit is considered to occur.

[0088] The results are shown in Figure 7 .

[0089] Figure 7 : is a graph showing the relationship between the thickness of the solid electrolyte (SE) sheet after pressurization and the battery capacity in the examples and comparative examples. Figure 7 In the graph, the vertical axis represents the maximum value among the values ​​of battery capacity obtained in this test as 1, and each measured value is expressed as a relative value.

[0090] like Figure 7 As shown, it was confirmed that in the solid battery using the solid electrolyte sheet of the comparative example, if the thickness of the solid electrolyte layer is reduced, a short circuit will occur. In contrast, according to the solid battery using the solid electrolyte sheet of the embodiment, it was confirmed that a solid battery with a high battery capacity can be obtained without short circuiting regardless of the thickness of the solid electrolyte sheet.

[0091] Reference numerals

[0092] 1: Base material

[0093] 2,20: Slurry for solid electrolyte

[0094] 3: Scraper

[0095] 4: Drying device

[0096] 5,50: Three-dimensional structure

[0097] 6: Solid electrolyte layer

[0098] 10: Solid electrolyte sheet

Claims

1. A method for manufacturing a solid electrolyte sheet, wherein the solid electrolyte sheet is filled with a solid electrolyte, the manufacturing method comprising: The first step is to apply a slurry containing a solid electrolyte onto a substrate; A second step of forming a solid electrolyte layer by drying the slurry on the substrate; A third step is to stack a thin sheet-like three-dimensional structure on the upper surface of the solid electrolyte layer; A fourth step is to apply a slurry containing a solid electrolyte to the interior and upper portion of the three-dimensional structure; and A fifth step is to obtain a solid electrolyte sheet filled with a solid electrolyte by drying the slurry inside and on the top of the three-dimensional structure. In the fourth step, the slurry containing the solid electrolyte is applied so that the three-dimensional structure is provided at the center portion in the thickness direction of the solid electrolyte sheet.

2. The method for manufacturing a solid electrolyte sheet according to claim 1, wherein the thickness obtained by subtracting the thickness of the three-dimensional structure from the total coating thickness of the slurry containing the solid electrolyte when applied in the fourth step is the coating thickness of the slurry containing the solid electrolyte when applied in the second step. 3 . The method for producing a solid electrolyte sheet according to claim 1 , wherein the three-dimensional structure is a nonwoven fabric.